Assessment of physical activity and abdominal obesity among elderly in Pondok Institutions, Kelantan - Rahim, Anis Azira Mohd (Universiti Sains Malaysia, 2015)
Abdominal obesity and physical inactivity in elderly are linked with greater mortality risk. For elderly, it is essential for them to improve their physical activity level toward a better health. This study aimed to find the association between abdominal obesity and physical activity level among elderly in Pondok Institutions, Kelantan. Seventy-one respondents (6 males and 65 females) of Malaysian elderly aged 60 years old and above in Pondok Institutions, Kelantan were selected using convenient sampling method. Respondents were interviewed for their physical activity level using International physical activity questionnaire for seniors (IPAQ-E) Bahasa Melayu Short Version, and Mini Nutritional Assessment (MNA) to assess their nutritional status. Weight, height, and waist circumference were measured to calculate Body Mass Index (BMI) and abdominal obesity. The 24 hours dietary recall was used to determine the daily energy intake of the elderly. Based on BMI classification, the respondents were categorized into underweight (9.9%), normal weight (45.1%), overweight at risk (26%), obese I (7.0%), and obese III (1.4%). The percentage of abdominal obesity among elderly in Pondok institutions, Kelantan was 59.2%, while for the percentage of physical activity level among elderly in Pondok institutions, Kelantan were 52.1% for Inactive Category 1, 47.9% for Moderately Active Category II, and 0% for HEPA Active Category III. MNA result showed that 49.3% of them have normal nutritional status, 47.9% were at risk of malnutrition, and 2.8% were malnourished. There was significant association between physical activity and abdominal obesity among elderly in Pondok institutions, Kelantan. The finding also showed significant association between BMI and abdominal obesity. It was also found that there was no significant association between abdominal obesity, physical activity level, and nutritional status between male and female elderly in Pondok institutions, Kelantan. In conclusion, abdominal obesity and physical activity level among elderly in Pondok Institutions, Kelantan do have significant association.